(untitled) (Applied Biological Research, 2015)
The shelf life and bioefficacy of Rhizobium leguminosarum loaded on various carriers was assessed under laboratory and field conditions at JNKVV, Jabalpur (India). The carriers tested were lignite, coal, vermi compost, poultry manure, dolomite, Azolla, lignite + coal, lignite + vermi compost, lignite + poultry manure, lignite + dolomite and Azolla + lignite. leguminosarum culture isolate G4 was multiplied in YEM broth under aseptic conditions and after specified growth, the rhizobial liquid broth was mixed with eleven carriers, each separately, in a ratio to obtain 40% moisture in the finished product. The initial rhizobial population in the finished product was estimated before final packing and storage. For shelf life assessment, the samples were drawn from the stored productsat 30 days intervals upto 180 days and rhizobial population assessed. The bioefficacy of carrier loaded R. leguminosarum biofertilizers were studied in field on chickpea variety JG-74. The nodule number plant-1, nodule dry weight plant-1 and nitrogen content in nodules were recorded 45 days after sowing (DAS) while grain yield, total biomass, nitrogen content in seed and straw and total nitrogen uptake were studied at harvest. Lignite proved best carrier followed by coal, while other indigenous carriers failed to support rhizobia. Use of these carrier materials in conjunction with lignite (1:1) did not yield satisfactory results. It may be concluded that vermicompost, poultry manure, dolomite and Azolla cannot substitute lignite as a carrier for rhizobial inoculants, although coal proved safe for this purpose.